UNDERSTANDING CCE IN THE CONTEXT OF RTE-2009 - MANJU JAIN (THE PRIMARY TEACHER, 2025)
The Right of Children to Free and Compulsory Education Act-2009 (RTE Act-2009), implemented since April 2010, has made elementary education a Fundamental Right to all children in the age group of six to fourteen years. Chapter V of the Act on Curriculum and Completion of Elementary Education under Section 29 (1) (h) provides for Comprehensive and Continuous Evaluation of child’s understanding of knowledge and his or her ability to apply the same. In view of this, various efforts have been made by states and UTs to develop CCE materials and evolve strategies for its implementation. The analysis of materials developed in this area by states and UTs and the field experiences suggested that teachers are facing problems in the understanding and implementation of CCE in classrooms. Different kinds of prescriptive formats have been developed for teachers to record the progress of children. As a result of this, teachers are engaged more in compiling the data for CCE during the teaching learning time. The reporting procedures have also been found to be mechanical and cumbersome exercise for teachers. Apart from this, there are misconceptions related to various terms such as a continuous, comprehensive, evaluation, assessment, formative and summative assessment, which created confusion in the system and practitioners are interpreting CCE in their own way